High-temperature equation of state of vanadium. Issue 1 (2nd January 2016) - Crichton, W. A.; Guignard, J.; Bailey, E.; Dobson, D. P.; Hunt, S. A.; Thomson, A. R.
ABSTRACT: The unit cell dimensions of vanadium, NaCl and Au have been collected to 11. 5 GPa and 1000 K by powder X-ray diffraction and are used to constrain a practical high-temperature EoS for bcc vanadium. The resulting third-order Birch–Murnaghan EoS is described with parameters KT 0, 300  = 150.4 ± 6.2 GPa, K T ′  = 5.5 ± 1.0, α 0  = 4.8(6)·10 −5, α 1  = −2.4(9)·10 −8 and δKT δT  = −0.0446(7) GPa/K. The parameter α . K 0, 300 is 616·10 −5  K −1  GPa and reduces to zero at an estimated 60 GPa at RT. This EoS description is entirely consistent with the majority of X-ray, ultrasonic, shock wave and calculated data-sets in this p, T range. These measurements facilitate the estimation of in situ temperatures under high pressures when vanadium is used inside sample assemblies and are useful, when used with h -BN, to estimate p, T over the full range of h -BN stability.